A interferência do internetês na escrita: uma proposta para o ensino fundamental II - Soares, Gislene Fraga dos Reis (2021)
The implications due to the interference of the internet language in the writing of elementary school students II and caused by the growing and frequent exposure to the internet and to the use of language characteristic of social networks served as the motto for this research, which was inspired by the reflective observations of our teaching practice in the classroom and by the recurrent verification of writing inherent to the internet language in the daily production of texts by Basic Education students. We understand that these students do not have a clear perception of the appropriate moments to use the prestigious variety of the language or to use the language variety typical of internet language and common to digital social networks. In this context, we started from the hypothesis that the elaboration of a pedagogical proposal focused on the work of internet language in the classroom would be an important contribution to teaching practice. Thus, considering the use of technologies at school, our study aimed to develop a pedagogical proposal highlighting internet language as a diaphasic and diamestic linguistic variation. The study of internet language, its definitions and what would be the implications of transferring its use — generally used in digital social networks — to writing, constitute important points in our research. The theoretical foundation that supported our work draws on contributions from several scholars, which are: Barbosa (2001), Biderman (2001), Bisognin (2009), Bortoni- Ricardo (2004 and 2005), Coseriu (1978), Cristianini (2007), Faraco (2008 and 2015), Freitas; Costa (2006), Galli (2005), Komesu; Tenani (2015), Marcuschi (2005 and 2008), among others. Methodologically, the study is an exploratory research, with a qualitative approach and an applied nature. Our pedagogical proposal consists in the elaboration of the “Teacher Support Material” aimed at Portuguese Language teachers and the “Activity Book” for the Student. Both are divided into two parts. The first part consists of the Activity Book which presents a script containing ten pedagogical workshops and the second part offers guidelines that lead to our digital educational tool in quiz format. Therefore, we intend to collaborate with the teacher to provide students with the following reflection: the transposition of the internet language to textual productions at school, and beyond, is not suitable in contexts that require the use of the prestige norm of the language.